AGE AND GEOCHEMISTRY OF BASALT-CHERT ASSOCIATIONS IN THE OPHIOLITES OF THE IZMIR-ANKARA MÉLANGE EAST OF ANKARA, TURKEY: PRELIMINARY DATA - Bortolotti, Valerio; Chiari, Marco; Göncüoglu, M. Cemal; Marcucci, Marta; Principi, Gianfranco; Tekin, U. Kagan; Saccani, Emilio; Tassinari, Renzo (Ofioliti, 2013)
In this paper, we present the preliminary data on the age of the radiolarian cherts deposited on top of basalts belonging to the Eastern Ankara Mélange (part of the Izmir-Ankara Mélange). Petrological studies on the basalts were carried out in order to constrain the tectonic setting of the studied basalt-chert sequences. Nine sections were sampled East of Ankara and twenty seven samples were collected for biostratigraphic and geochemical analyses. The oldest radiolarian cherts dated in the present paper are referable to the Late Triassic (Section 6: late Norian) and are associated with basaltic rocks of OIB character. OIB type volcanic rocks are also found in other sections, associated with cherts of Late Jurassic (Section 3: middle-late Oxfordian to late Kimmeridgian-early Tithonian) and Early Cretaceous (Section 1: late Valanginian to late Hauterivian) ages. E-MORB type rocks are associated with radiolarian cherts of Cretaceous age (Section 4: middle late Barremian-early early Aptian and Section 7: Valanginian to middle Aptian-early Albian), whereas the oldest N-MORBs were found in a section of Late Jurassic age (Section 5: early-early late Tithonian). Other N-MORBs are associated with radiolarian cherts of Early Cretaceous age (Section 8: late Valanginian-early Barremian). P-MORBs type rocks were found only in a section of Middle Jurassic age (Section 2: early-middle Bajocian to late Bathonian-early Callovian age). In this work, we document the occurrence of Late Triassic OIB-type rocks and of rocks showing different geochemical affinities (N-, E-, P-MORBs and OIB) generated within the same time span (Middle-Late Jurassic - Early Cretaceous). N-MORBs are compatible with composition of melts generated by partial melting of a depleted MORB mantle source. In contrast, OIBs are compatible with partial melting of an enriched-type mantle source. E-MORBs may have derived from mantle source slightly enriched with respect to a DMM source, whereas P-MORBs are compatible with melts generated from a mantle source significantly enriched, compared to DMM.